2022
DOI: 10.1002/hep4.2019
|View full text |Cite
|
Sign up to set email alerts
|

NPRL2 down‐regulation facilitates the growth of hepatocellular carcinoma via the mTOR pathway and autophagy suppression

Abstract: Hepatocellular carcinoma (HCC) is a highly invasive malignancy. Recently, GATOR1 (Gap Activity TOward Rags 1) complexes have been shown to play an important role in regulating tumor growth. NPRL2 is a critical component of the GATOR1 complex. Therefore, this study used NPRL2 knockdown to investigate how GATORC1 regulates the prognosis and development of HCC via the mammalian target of rapamycin (mTOR) and autophagy signaling pathways. We established HepG2 cells with NPRL2 knockdown using small interfering RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…mTOR activity is inhibited by NPRL2 by interacting and directly binding with Rag GTPase, RagD in particular, and interferes with mTOR activity (29). mTOR was found to be downregulated in NPRL2-restored A549-NPRL2 ++/++ , which was consistent with others (12,32), whereas knocking down NPRL2 increased the Rag GTPases and mTOR activation (24). This mTOR downregulation was found to be associated with decreased expression of downstream mediators including phospho-S6, phospho-4E-BP1, phospho-PRAS40, and phospho-GSK-3β in NPRL2 restored cells.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…mTOR activity is inhibited by NPRL2 by interacting and directly binding with Rag GTPase, RagD in particular, and interferes with mTOR activity (29). mTOR was found to be downregulated in NPRL2-restored A549-NPRL2 ++/++ , which was consistent with others (12,32), whereas knocking down NPRL2 increased the Rag GTPases and mTOR activation (24). This mTOR downregulation was found to be associated with decreased expression of downstream mediators including phospho-S6, phospho-4E-BP1, phospho-PRAS40, and phospho-GSK-3β in NPRL2 restored cells.…”
Section: Discussionsupporting
confidence: 90%
“…The TME was significantly altered when NPRL2 was permanently restored, which was characterized by increased pro-immunogenic signatures including increased TILs, CD8 + T, and HLADR + DC, which led to significantly reduced tumor growth in humanized mice. On the contrary, the knockdown of NPRL2 promoted cell growth and proliferation in vitro and in vivo (24). Ingenuity pathway analysis showed the significant downregulation of pro-tumorigenic TGFβ1, TGFβ2, and CD47 signaling in anti-PD1 resistant tumors after NPRL2 gene therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 , 22 ] Similarly, TM6SF1, NEU1, NPRL2, and TMEM106B, as key genes for lysosome formation, could enhance lysosomal function and thus further regulate tumor progression. [ 23 , 24 ] Epithelial mesenchymal transition (EMT), a crucial stage in building the tumor microenvironment, plays an integral part in the progression of LUAD. Yuan et al found that Glypican-5, an oncogene, could inhibit the process of EMT in lung cancer, so as to suppress tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%